Hairspray [videorecording] ([S.l] : New Line Cinema, 2007)
It's 1962 and change is in the air in Baltimore, Tracy Turnblad, a girl with big hair and big dreams, has only one passion in life - to dance on "The Corny Collins Show." When her chance arrives, she grooves her way into instant stardom and the eyes of teen dream Link Larkin (Zac Efron). But with the program's scheming stage manager, (Michelle Pfeiffer) against her, trend-setting Tracy will need help of her best friend Penny (Amanda Bynes), her big-hearted mother (John Travolta) and sassy co-host Motormouth Maybelle (Queen Latifah) to show the world that all it takes to make a dream come true is a toe-tappin' beat and a little HAIRSPRAY!
Keywords: Teenage girls -- Maryland -- Baltimore -- Drama; Teen television programs -- Maryland -- Baltimore -- Drama